Spatial Parameters And Connection Availability In Ad Hoc Networks - Trajanov, Dimitar; Filiposka, Sonja; Makraduli, Jani; Grnarov, Aksenti (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2003)
The fluctuation of the ad hoc network spatial parameters not only alters the network topology but also introduces severe changes in the ad hoc network performances. Based on a given ad hoc network connection availability model, in this paper we investigate the influence of several spatial parameters that affect the ad hoc network connection availability which is often used as an important measure of the ad hoc networks fault tolerance. These parameters include: size of the area wherein the participants in the mobile ad hoc network are scattered, node density, transmission range, distance between the communicating nodes.
Keywords: mobile ad hoc networks, connection availability model, spatial parameters